وحدة تجريبية لمعالجة المياه الملوثة باستخدام التهوية والمناخل البلاستيكية كحوامل بيولوجية - جنيدي, حسين; معروف, مروه (Latakia University Journal -Engineering Sciences Series, 2018)
تم إنشاء وتشغيل وحدة معالجة تجريبية لدراسة إمكانية معالجة المياه الملوثة معالجة بيولوجية عن طريق استخدام النمو المعلق والنمو الملتصق. تتألف الوحدة التجريبية من وحدة ترذيذ تؤمن ترطيب الحوامل البيولوجية، وتوزيع المياه بشكل متجانس عليها بالإضافة إلى زيادة تركيز الأوكسجين المنحل في المياه، يليها مرشح زود بوسائط للنمو البيولوجي الملتصق. بلغت مساحة الحوامل m2(13) تقريباً، والتي تم تنمية الغشاء البيولوجي عليها بحيث تقوم البكتيريا الموجودة في الغشاء بتفكيك المادة العضوية وصولاً إلى إرجاع النترات إلى نتريت ثم إلى غاز النتروجين. يلي المرشح حوض تهوية يؤمن معالجة المياه عن طريق النمو المعلق. تم تركيب أجزاء الوحدة وتشغيلها بالاعتماد على مياه الصرف الصحي المأخوذة من غرفة التفتيش الموجودة بالقرب من الوحدة السكنية رقم (18). بلغت الكفاءة الوسطية لإزالة الـ BOD5 69.4%، بينما بلغت الكفاءة الوسطية لإزالة شاردة النترات 34%. بينت النتائج أن استخدام هذا النظام يحسن من مواصفات المياه الملوثة . A pilot unit was constructed and operated to study the ability of treating polluted water using biological treatment. The experimental unit consists of water sprayer unit that ensure wetting of the filtered media and distributing water in a homogenous manner as well as increasing the dissolved oxygen concentration in water. The sprayer unit is followed by a biological filter; the area of the filtered media was (13) m2. The developed biological film placed on the filtered media will dismantle the organic matter, which reduce nitrates to nitrite then to a nitrogen gas. The filter was connected to an aeration basin where the suspended growth was archived. The pilot unit was operated depending on the water was taking from a manhole nearby the residential unit number 18. The average efficiency of BOD5 removing was 69.4% and of nitrate, removing was 34%. The results showed that this system can improve water's characteristics.